Reliability and detecting change following short-term creatine supplementation: Comparison of two-component body composition methods - Kilduff, L. P.; Lewis, S.; Kingsley, M. I. C.; Owen, N. J.; Dietzig, R. E. (The Journal of Strength and Conditioning Research, 2007)
The purpose of the present study was twofold: firstly, to assess the reliability of various body composition methods, and secondly, to determine the ability of the methods to estimate changes in fat-free mass (FFM) following creatine (Cr) supplementation. Fifty-five healthy male athletes (weight 78.3 +/- 10.3 kg, age 21 +/- 1 years) gave informed consent to participate in this study. Subjects' FFM was estimated by hydrostatic weighing (HW), air-displacement plethysmography (ADP), bioelectrical impedance analysis (BIA), near-infrared spectroscopy (NIR), and anthropometric measurements (ANTHRO). Measurements were taken on 2 occasions separated by 7 days to assess the reliability of the methods. Following this, 30 subjects returned to the laboratory for an additional test day following 7 days of Cr supplementation (20 g[middle dot]d-1 Cr + 140 g[middle dot]d-1 dextrose) to assess each method's ability to detect acute changes in FFM. In terms of reliability, we found excellent test-retest correlations for all 5 methods, ranging from 0.983 to 0.998 (p < 0.001). The mean biases for the 5 methods were close to 0 (range - 0.1 to 0.3 kg) and their 95% limits of agreement (LOAs) were within acceptable limits (HW = -1.1 to 1.7 kg; ADP = -1.1 to 1.2 kg; BIA = -1.0 to 1.0 kg; NIR = - 1.4 to 1.4 kg); however, the 95% LOAs were slightly wider for ANTHRO (- 2.4 to 2.6 kg). Following Cr supplementation there was a significant increase in body mass (from 77.9 +/- 10.1 kg to 78.9 +/- 10.3 kg, p = 0.000). In addition, all 5 body composition techniques detected the change in FFM to a similar degree (mean change: HW = 0.9 +/- 0.6 kg; ADP = 0.9 +/- 0.6 kg; BIA = 0.9 +/- 0.6 kg; NIR = 0.8 +/- 0.5 kg; ANTHRO = 1.0 +/- 0.7 kg; intraclass correlation coefficient = 0.962). We conclude that between-day differences in FFM estimation were within acceptable limits, with the possible exception of ANTHRO. In addition, all 5 methods provided similar measures of FFM change during acute Cr supplementation.